SIMULASI PENGARUH VARIASI EKSTRAKSI TURBIN TERHADAP EFISIENSI TERMAL SISTEM PLTU BARRU MENGGUNAKAN MATLAB/SIMULINK - Remigius Tandioga; Apollo Apollo; Rian Pratama; Eko Kurnala (Politeknik Negeri Ujung Pandang, 2016)
Basically extraction turbine is the process of utilization of residual steam from the turbine or steam thermal energy transfer that had crashed into the turbine blade to produce rotation. Before the water is pumped into the boiler feedwater must be preheated until it reaches a certain temperature. The heating takes place by conduction by using hot steam removed (extracted) from the turbine.Retrieval of data taken at the turbine extraction system in the plant Barru. The data is in the form of temperature, pressure, flow rate, and volume as well as an image extraction turbine system. Then to develop a model in the form of a mathematical model extraction component. Further making and testing programs in the form of block Simulink simulation using MATLAB software. Perform data processing and discussion. From the simulation results will be obtained data and charts thermal efficiency of the turbine and the variation of the use of extraction will be conducted discussion. The conclusion of this study is variable extraction systems have been conducted using a manual counting of steam calculator software and a conventional formula. Variable values that have been obtained in the form= 14,95 kg/s,= 0,882 kg/s,= 4,764 kg/s,= 1,742 kg/s,= 52,905 kg/s,= -33,436 kg/s, Wp total = 15,957 kJ/kg, Qin = 2650,852 kJ/kg. Mathematical model extraction turbines are known in the form of the transfer function. The simulation results obtained with the use of thermal efficiency value of one to six extraction, with details Eks1 = 15,5%, Eks2 = 21,27%, Eks3 = 21,46%, Eks4 = 22%, Eks5 = 42%, Eks6 = 54%. From these results it is evident that the use of feedwater heater as a component of the extraction system is essential to improve the thermal efficiency of a steam power plant, especially in plant Barru.Keywords: Barru power plant, extraction, MATLAB Simulink, Thermal Efficiency.